Pengaruh Celebrity Endorser, Content Marketing dan Brand Love Terhadap Purchase Decision Melalui Purchase Intention Sebagai Intervening - Marlinda, Nanda; Arsyad, Annisa Wahyuni (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This research aims to find out whether there is an influence of celebrity endorser, content marketing and brand love on purchase decisions through purchase intention as an intervention for consumers of Azarine Sunscreen Series products in Samarinda City. This research uses quantitative methods by collecting data by distributing questionnaires to respondents. The research was conducted on 150 respondents aged 17 - 41 years who live in Samarinda City and have purchased Azarine Sunscreen Series products. The sampling technique used in this research is non-probability sampling with a purposive sampling method. The data that has been collected is then processed using the SmartPLS 4.1.0.9 analysis tool with the Structural Equation Modeling (SEM)-PLS method which consists of testing the measurement model (outer model), testing the structural model (inner model) and testing hypotheses. The results of this research show that: (1) Celebrity endorser have a significant and negative effect on purchase intention, (2) Content marketing has a significant and positive effect on purchase intention, (3) Brand love has a significant and positive effect on purchase intention, (4) Celebrity endorser significant and negative influence on purchase decisions, (5) Content marketing has a significant and positive influence on purchase decisions, (6) Brand love has a significant and positive influence on purchase decisions, (7) Purchase intention has a significant and positive influence on purchase decisions, (8) Celebrity endorser have a significant and negative influence on purchase decisions through purchases intention, (9) Content marketing has a significant and positive effect on purchase decisions through purchase intention, (10) Brand love has a significant and positive effect on purchase decisions through purchase intention.